Infotech@Aerospace 2005
DOI: 10.2514/6.2005-7002
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Data-Driven Prognostics

Abstract: Integrated Systems Health Management includes fault detection, fault diagnosis (or fault isolation), and fault prognosis. We define prognosis to be detecting the precursors of a failure, and predicting how much time remains before a likely failure. Algorithms that use the data-driven approach to prognosis learn models directly from the data, rather than using a hand-built model based on human expertise. This paper surveys past work in the datadriven approach to prognosis. It also includes related work in data-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
149
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(166 citation statements)
references
References 18 publications
0
149
0
3
Order By: Relevance
“…The Condition Monitoring Sensors (CMS) attached to the components continuously send the readings of the state of the components via the SCADA systems and store the data in databases or clouds as big data. Processing of these data is vital for the prediction of the future state of the components, which is done by using different models such as ANN, Support Vector Machine (SVM), Gradient Boosting Machine (GBM), Deep Learning (DL), Random Forest (RF), the Generalized Linear Model (GLM), Grid Search (GS) and Statistical Matching Performance Pattern (SMPP) [8,25,26,[29][30][31][32][33].…”
Section: Framework For Complex System's Prognosismentioning
confidence: 99%
“…The Condition Monitoring Sensors (CMS) attached to the components continuously send the readings of the state of the components via the SCADA systems and store the data in databases or clouds as big data. Processing of these data is vital for the prediction of the future state of the components, which is done by using different models such as ANN, Support Vector Machine (SVM), Gradient Boosting Machine (GBM), Deep Learning (DL), Random Forest (RF), the Generalized Linear Model (GLM), Grid Search (GS) and Statistical Matching Performance Pattern (SMPP) [8,25,26,[29][30][31][32][33].…”
Section: Framework For Complex System's Prognosismentioning
confidence: 99%
“…They validate their models using induced faults from a laboratory setting. Schwabacher [33] has made a survey of artificial intelligence (AI) for failure prognosis and concluded that for realistic systems ''fully implementing prognosis is very difficult''. Several researchers have stated their intention to do prognostics, and have described the progress they have made in fault detection, but have left estimation of useful life remaining to future work.…”
Section: Dm For Zdmmentioning
confidence: 99%
“…Machine Prognostics and Health Management (PHM) is the process of detecting abnormal conditions, diagnosis of the fault and their cause and prognostics of future fault progression, as reviewed by Tobon-Mejia et al (2012), Heng et al (2009) and Schwabacher (2005). Maintenance strategies can be classified into three categories 1) Breakdown maintenance, 2) Preventive maintenance and 3) Condition-based maintenance (CBM) Jardine et al (2006).…”
Section: Introductionmentioning
confidence: 99%